2005
DOI: 10.2165/00044011-200525070-00003
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy of a Fixed-Dose Combination of Trandolapril-Verapamil in Patients with Stage 2 Hypertension Inadequately Controlled by Monotherapy

Abstract: A fixed-dose combination of trandolapril-verapamil seems to be an effective and safe option for the management of stage 2 hypertension in Mexican patients uncontrolled by monotherapy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2008
2008
2020
2020

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 11 publications
0
4
0
Order By: Relevance
“…In a similar study conducted by Rubio-Guerra et al, the fixed-dose combination of trandolapril 2 mg and verapamil 180 mg was also found to be effective in the control of hypertension, with most patients having significant BP reductions and reaching the recommended therapeutic goals [ 16 ]. In the Tr/Ve study [ 17 ] conducted for the evaluation of the efficacy and safety of the verapamil SR and trandolapril combination, it was shown that the combination therapy in a single pill in the SR formulation was more effective than the use of the active ingredients of the combination and placebo in 631 patients with hypertension through 10 weeks of therapy.…”
Section: Discussionmentioning
confidence: 99%
“…In a similar study conducted by Rubio-Guerra et al, the fixed-dose combination of trandolapril 2 mg and verapamil 180 mg was also found to be effective in the control of hypertension, with most patients having significant BP reductions and reaching the recommended therapeutic goals [ 16 ]. In the Tr/Ve study [ 17 ] conducted for the evaluation of the efficacy and safety of the verapamil SR and trandolapril combination, it was shown that the combination therapy in a single pill in the SR formulation was more effective than the use of the active ingredients of the combination and placebo in 631 patients with hypertension through 10 weeks of therapy.…”
Section: Discussionmentioning
confidence: 99%
“…Clinical studies and observational analyses have also demonstrated the beneficial effects of fixed-dose therapy on BP control rates [17][18][19]. In addition, there are data showing that fixed-dose combination therapy may achieve BP control more promptly than the standard practice of starting with a single agent, titrating, and then adding a second drug [20][21][22].…”
Section: Rationale For the Use Of Combination Therapy In Stage 2 Hypementioning
confidence: 99%
“…Clinical trials in patients with stage 2 hypertension have consistently shown the benefit of combining a CCB with an ACE inhibitor 35,46,47 . Recent trials have also established the efficacy and tolerability of combining an ARB with a CCB in high‐risk populations, including patients with stage 2 hypertension 41,42,48 …”
Section: Clinical Trials Of Ccbs Plus Ras Inhibitors In High‐risk Popmentioning
confidence: 99%